2022
DOI: 10.1039/d2tc00848c
|View full text |Cite
|
Sign up to set email alerts
|

Octahedral tilting in Prussian blue analogues

Abstract: Octahedral tilting is key to the structure and functionality of perovskites. Here we show how these distortions manifest in the related Prussian blue analogues (PBAs): cyanide versions of double perovskites...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 88 publications
8
46
0
Order By: Relevance
“…However, achieving this capacity is extremely difficult due to the presence of [Fe(CN) 6 ] n− vacancies (Hurlbutt et al, 2018). Furthermore, the presence of severe phase transitions which damage the structure during operation in a battery is strongly dependent on the A + cation and [M′(CN) 6 ] n− vacancy content (Rudola et al, 2017;Tapia-Ruiz et al, 2021;Boström and Brant 2022). Despite the importance of PBAs, their accurate and consistent compositions are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, achieving this capacity is extremely difficult due to the presence of [Fe(CN) 6 ] n− vacancies (Hurlbutt et al, 2018). Furthermore, the presence of severe phase transitions which damage the structure during operation in a battery is strongly dependent on the A + cation and [M′(CN) 6 ] n− vacancy content (Rudola et al, 2017;Tapia-Ruiz et al, 2021;Boström and Brant 2022). Despite the importance of PBAs, their accurate and consistent compositions are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of PBAs, their accurate and consistent compositions are rarely reported. This was highlighted by a recent meta-study on the reported structures of PBAs as a function of composition (Boström and Brant 2022). When clear trends emerged, quantitative conclusions became difficult to be drawn due to uncertainties on the reported compositions.…”
Section: Introductionmentioning
confidence: 99%
“… 25 Formally, this monoclinic structure type is related to the idealized cubic PBA parent structure ( Fm 3̅ m symmetry) by the combined activation of the slide distortion shown in Figure 1 b and a cooperative a 0 a 0 c + octahedral tilt of the framework structure that always seems to accompany it. 22 , 23 The former deformation transforms as the X 5 + irreducible representation (irrep; note that we are using labels relative to the double-perovskite Fm 3̅ m parent with B-site ions located at the cell origin) and the latter as X 3 + ; it is the interplay of these two distortion modes that reduces the PBA symmetry to P 2 1 / n . 22 Replacing Mn 2+ by the Jahn–Teller-active Cu 2+ understandably leads to an additional distortion of the type illustrated in Figure 1 c, which transforms as Γ 3 + .…”
Section: Results and Discussionmentioning
confidence: 99%
“…As a final point, we note that not only are the K-ion slides the key thermally activated distortion in this material, but also that the observed transition to Cccm implies it is probably right to think of them as a fundamental distortion in their own right and not simply a byproduct of other distortions, such as tilts. 23 …”
Section: Results and Discussionmentioning
confidence: 99%
“…It has recently been shown that PBAs with a low [Fe(CN) 6 ] vacancy and high A-site cation content undergo a structural distortion from cubic symmetry with an associated volume change. 13 The severity of this phase transition depends upon whether the material is hydrated or dehydrated, with the dehydrated samples exhibiting volume changes up to 18%. 7,14 This distortion is removed during extraction of the A-site cation and subsequently leads to strain build up, capacity fade and poor cycling stability.…”
Section: Introductionmentioning
confidence: 99%